The outcome of exposure technique adjustment toward the deviation index and national diagnostic reference levels from digital chest radiographs in Lomkao Crown Prince Hospital - Seetasung, Suwanai (The Thai Journal of Radiological Technology, 2024)
Introduction: The Deviation Index (DI) plays a crucial role in digital imaging systems, guiding the selection of optimal radiographic techniques. Objective: This study aimed to optimize the chest postero-anterior (PA) X-ray radiographic technique with the optimal DI value as per AAPM recommendations, ensuring that the Entrance Skin Air Kerma (ESAK) stays within specified exposure limits. Furthermore, the study sought to compare the DI values before and after adjusting the exposure techniques. Methods: The radiographic parameters for chest PA X-ray were optimized by varying kVp and mAs while exposing a phantom. The ESAK and DI were recorded for each combination of exposure techniques. An appropriate exposure technique, according to the AAPM standard that determines the DI criteria which to be between ±3 and an ESAK value not exceeding 0.4 mGy, was selected after the adjustment was performed. The original and adjusted exposure techniques were then applied to two patient groups, each consisting of 34 patients. Subsequently, a comparison was made between the original and the adjusted technique values. Results: The default exposure technique was 117.41±1.51 kVp and 3.7±0.76 mAs, resulting in chest radiographs with an average DI of -4.11±0.91 and an ESAK value at the median of 0.22 mGy. After adjusting the exposure technique to 124 kVp and 4.5 mAs, the average DI was -2.38±0.53, and the ESAK value at the median was 0.27 mGy. When comparing the average DI values and the percentage of images meeting AAPM standards before and after modifying the exposure technique, a statistically significant difference was observed (p-value<0.001). The number of radiographs with DI values within the AAPM standard increased to 85% of the total images, compared to 8% with the default exposure technique. Conclusion: The adjusted radiographic technique for chest radiographs achieves DI values within the standard criteria of AAPM and keeps ESAK values below the suggested reference level (Thailand DRLs 2023). Furthermore, the image quality is superior to that of the original technique. Therefore, this study recommends the adoption of the adjusted radiographic technique for digital chest radiography.